Initial screening of vegetable amaranth landraces towards extending the vegetable list - Das, Saubhik (Current Botany, 2017)
Vegetable amaranth is considered as one of the most favorite vegetables in the world, especially in the hot and humid tropical regions of the globe. Two of them are most popular i.e., Amaranthus tricolor and Amaranthus blitum, both are represented by a large number of morphotypes or landraces or varieties, which are taxonomically ill-defined, many of them are consumed as palatable vegetables as they look like the conventional cultivars. Due to wide morphological diversity and presence of many synonyms both the species are supposed to represent two species complex or aggregates viz., â€œTricolor complexâ€ and â€œBlitum complexâ€. Two new species have been identified from their landraces. In the present investigation morphometric analysis along with biochemical and molecular methodologies were applied to explore the relative closeness among few well known, popular vegetables and few less known landraces for better utilization of the crop biodiversity of vegetable amaranths. The experimental data were statistically analyzed and separate Dendrograms were computed on three parameters (Morphology, Isozyme polymorphism and ISSR band profile).The members of â€œTricolor complexâ€ were clustered together in a single group along with two newly introduced species A. bengalense (a member of â€œBlitum complexâ€) and A. parganensis (a gynomonoecious member of â€œTricolor complexâ€). Tricolor complex represents a plexus of species with varying sexual behavior from gynomonoecy to monoecy and indicates probable origin of monoecious Â Amaranthus tricolor varieties or landraces from gynomonecious member like A. parganensis as recent introduction. The study indicated a close alliance between A. bengalense, A. parganensis, A. tricolor landrace and popular A. tricolor varieties which consolidated the feasibility of utilizing the landrace and newly introduced species as potential vegetable.